Efficient synthesis of malonate functionalized chiral phosphapalladacycles and their catalytic evaluation in asymmetric hydrophosphination of chalcone - Li, Xi-Rui (2020)
Four chiral phosphapalladacycle complexes functionalized with the malonate moiety at the chiral carbon have been synthesized via a consecutive asymmetric hydrophosphination and cyclometallation protocol. High conversions were achieved in the P–H addition reaction, which was itself catalyzed by a phosphapalladacycle. Moderate to good enantioselectivities, were obtained for this step depending on the nature of the functional groups present on the naphthalene backbone. In contrast, the outcome of the subsequent cyclometallation reaction relies highly on the character of the functional groups. The catalytic potential of the synthesized phosphapalladacycle complexes was evaluated in the hydrophosphination reaction of chalcone with moderate results.